2022
DOI: 10.3389/fpsyg.2022.804349
|View full text |Cite
|
Sign up to set email alerts
|

Does Tourism Induce Sustainable Human Capital Development in BRICS Through the Channel of Capital Formation and Financial Development? Evidence From Augmented ARDL With Structural Break and Fourier-TY Causality

Abstract: The motivation of the study is to explore the nexus tourism-led sustainable human capital development (HCD) in Brazil, Russia, India, China, and South Africa (BRICS) for the period 1984–2019. The study applied several econometrical techniques for exposing the empirical association between tourism and HCD, such as the conventional and structural break unit root test, the combined cointegration test, long-run and short-run coefficients detected through implementing the Augmented Autoregressive Distributed Lagged… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
48
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(59 citation statements)
references
References 86 publications
(107 reference statements)
10
48
1
Order By: Relevance
“…The research concluded that an increase of 10% in energy use would hasten environmental degradation by releasing carbon into the atmosphere at a rate of 2.14 and 1.79 percentage points, respectively. More contamination of the environment results from the use of energy in many economic activities [89,90]. This is because not all energy comes from sustainable sources.…”
Section: Dsur Long-run Estimatesmentioning
confidence: 99%
“…The research concluded that an increase of 10% in energy use would hasten environmental degradation by releasing carbon into the atmosphere at a rate of 2.14 and 1.79 percentage points, respectively. More contamination of the environment results from the use of energy in many economic activities [89,90]. This is because not all energy comes from sustainable sources.…”
Section: Dsur Long-run Estimatesmentioning
confidence: 99%
“…The ARDL approach has been extensively used in empirical studies investigating long-run associations (Qamruzzaman and Jianguo, 2018;Qamruzzaman and Karim, 2020a;Qamruzzaman and Karim, 2020b;. ARDL estimation provides certain benefits over traditional cointegration tests, including (1) efficient estimation regardless of the study's sample size (Ghatak and Siddiki, 2001;Rehman et al, 2021;Li and Qamruzzaman, 2022;Qamruzzaman, 2022;Xia et al, 2022),…”
Section: Cointegration Test Null Hypothesismentioning
confidence: 99%
“…To maintain national economic competitiveness in the face of growing global awareness of the effects of economic activity on resource consumption and the environment, new production and consumption patterns are becoming increasingly popular as a means of spurring innovation in business sector activities, particularly technology (Galende, 2006;Li and Qamruzzaman, 2022). The innovation process depends on external variables; the development of new technologies results from interactions with consumers, suppliers, rivals, and numerous other public and private organizations.…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
“…According to the endogenous economic growth hypothesis, an increase in expenditure on research and development (R&D) may enhance economic output efficiency and resource usage efficiency. Despite this, it is uncertain as to how much technical innovation can contribute to advances in environmental quality, especially in CO 2 emissions (Howitt, 2000;Pablo-Romero and Sánchez-Braza, 2015;Li and Qamruzzaman, 2022;Xia et al, 2022). Technology advancement is expected to boost productivity and efficiency during the Fourth Industrial Revolution as a supply-side miracle.…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
See 1 more Smart Citation